FRI0308 Corticosteroids combined with doublet or single-agent immunosuppressive therapy for active proliferative lupus nephritis. (12th June 2018) - Liu, B.; Yu, Y.; Tang, Y.; Fu, S.; Liang, P.; Xu, A.
Abstract : Background: Current evidence exploring whether corticosteroids (C) plus doublet immunosuppressive therapy (IT) is superior to the classical combination of C with single-agent IT for active proliferative lupus nephritis (LN) is controversial. Objectives: We aimed to clarify the efficacy and safety of C+doublet versus single-agent IT for active proliferative LN by a meta-analysis. Methods: We searched for randomised clinical trials that evaluated the benefits and risks of C+doublet versus single-agent IT for active proliferative LN. The primary outcome was overall response rate (ORR). The second outcomes were the change from baseline in Systemic Lupus Erythematosus Disease Activity Index (SLE-DAI) score, negative conversion ratio of anti–double-stranded DNA (anti-dsDNA), and adverse events. The quality of the evidence was evaluated with the GRADE framework. The PROSPERO registry number is CRD42017068491. Results: The analysis included 10 trials with 1587 unique patients. Compared with C+single agent IT, C+doublet IT was statistically significant with higher ORR (relative risk [RR], 1.22; 95% confidence interval [CI], 1.09 to 1.35; p < 0.0001; moderate certainty). In subgroup analysis, C+doublet IT without biologics resulted into significant higher ORR than C+single agent IT (RR, 1.30; 95% CI, 1.13 to 1.50; p < 0.0001; moderate certainty), while C+doublet IT including biologics improved ORR only for refractory severe LN (RR, 1.46; 95% CI, 1.09 to 1.96; p=0.012; very-low certainty). A larger change from baseline in SLE-DAI score (standardised mean difference, −0.49; 95% CI, −0.68 to −0.30; p < 0.0001; moderate certainty) and a higher negative conversion ratio of anti-dsDNA (RR, 1.34; 95% CI, 1.06 to 1.69; p=0.014; high certainty) were observed with C+doublet IT than with C+single agent IT. The rates of adverse events were similar between the two regimens (high to moderate certainty). Conclusions: Compared with single-agent IT, the combination of corticosteroids with doublet IT improved clinical outcomes for active proliferative LN. C+doublet IT including biologics may be a better regimen for refractory severe LN. There is imperative that prospective biomarker-driven trials to identify patients for whom C+doublet IT is most efficacious. Disclosure of Interest: None declared